Granular filtration of aerosols and hydrosols - Tien, Chi, 1930- (Butterworths series in chemical engineering.)
Granular filtration is a technique used extensively in the water and sewage industries, and we would all be quickly aware if it did not work properly. Designing and building an effective granular filter is a science and an art: this book covers both aspects. The theoretical basis of design is given considerable exposure, as are the behavioural characteristics of particles and fluids. This new edition contains extra material on stochastic simulations and the Lattice Bolzmann approach for studying deposition in granular media; more on prediction methods for collection efficiency; a chapter on the various available software programmes and a more industrial emphasis where appropriate. *New edition after over 15 years *New co-author *Still THE book on the subject.